Changes in household food and drink purchases following restrictions on the advertisement of high fat, salt, and sugar products across the Transport for London network: a controlled interrupted time series analysis. (November 2021) - Yau, Amy; Berger, Nicolas; Law, Cherry; Cornelsen, Laura; Greener, Robert; Adams, Jean; Boyland, Emma J; Burgoine, Thomas; de Vocht, Frank; Egan, Matt; Er, Vanessa; Lake, Amelia A; et al.
Abstract: Background: Restricting advertising of products with high fat, salt, and sugar (HFSS) content has been recommended as a tool to tackle obesity, but the impact on purchases is unknown. This study evaluates the impact of outdoor HFSS advertising restrictions, implemented across the London transport network in February, 2019, on HFSS purchases. Methods: Take-home food and drink purchase data (n=5 089 988) from 1970 households (London [intervention] n=977; North of England [control] n=993) from the Kantar Fast Moving Consumer Goods panel were analysed with a controlled interrupted time series design. We estimated average weekly household purchases of energy and nutrients from HFSS products in the postintervention period (Feb 25 to Dec 29, 2019) compared with a counterfactual constructed from the control and preintervention (June 18, 2018, to Feb 24, 2019) series. The London School of Hygiene & Tropical Medicine ethics committee approved the study (16297/RR/11721), and written informed consent was obtained from participants. Findings: After adjustment for confounders, average weekly household purchase of energy was reduced by 6·8% (1015·4 kcal, 95% CI 473·6–1557·2) compared with the counterfactual. Reductions in purchases of fat (57·4 g, 95% CI 21·7–93·0), saturated fat (26·4 g, 12·5–40·4) and sugar (85·5 g, 46·7–124·3) from HFSS products were also observed. When stratified by product category, we found a 19·4% reduction in energy purchased from chocolate and confectionery (317·9 kcal, 95% CI 200·0–435·8), along with reductions in fat (13·1 g, 95% CI 7·5–18·8), saturated fat (8·7 g, 5·7–11·7), sugar (41·4 g, 27·4–55·4), and salt (0·2 g, 0·1–0·2) purchased. Interpretation: To our knowledge, this was the first UK study to examine the impact of outdoor HFSS advertising restrictions on food and drink purchases. Our findings provide support for policies that restrict HFSS advertising as a tool to reduce purchases of HFSS products. However, the sustainability of the observed effects is unclear. Confounding due to other events occurring at the same time as the intervention in either the intervention or control group cannot be ruled out. However, observed intervention effects were greater among frequent public transport users, and were specific to the week the advertising restrictions were introduced. Funding: National Institute for Health Research School for Public Health Research (grant number PD-SPH-2015).